Approximate Solution of Volterra-Stieltjes Linear Integral Equations of the Second Kind with the Generalized Trapezoid Rule - Avit Asanov; Elman Hazar; Mustafa Eroz; Kalıskan Matanova; Elmira Abdyldaeva (Advances in Mathematical Physics)
The numerical solution of linear Volterra-Stieltjes integral equations of the second kind by using the generalized trapezoid rule is established and investigated. Also, the conditions on estimation of the error are determined and proved. A selected example is solved employing the proposed method.